Reducing Stunting Rates through Complementary Foods in Madukoro Village, Kajoran District, Magelang Regency - Sri Hananto Ponco Nugroho; Khabib Dimyati; Yasmin Firdauzi; Imam Aly (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Stunting is a chronic condition caused by long-term malnutrition. Stunting is based on the index of body length for age (PB/U) or height for age (TB/U) with a calculation limit (z-score) less than -2 SD. This community service aimed to provide information to the public about stunting, its impact, how to handle, and how to make complementary foods. The method used was survey, permission from partner, problem discussion, and problem solving by providing counselling and preparing complementary foods. The results indicated that people with insufficient understanding of stunting information were finally more aware of stunting, prevention methods, causes of stunting, and the impact of stunting on infants. By providing information about complementary foods, selecting nutritious foods, and environmental hygiene sanitation, stunting rates can be reduced in Madukoro Village.